The Usefulness of the Discrete Choice Experiment in Providing Effective Healthcare - Nikolina Dukić (Central European Public Administration Review)
Given that in times of crisis the burden of chronic disease is increasing, preventive interventions are becoming more important as they affect the maintenance and improvement of the population’s health, therefore reducing government spending on the sick leave and disability benefits. As public healthcare is characterized by administrative decision-making and relying on non-market mechanisms in the resource allocation, it requires the implementation of economic evaluations. This discussion shows that because the specifics of public healthcare complicate the data collection of revealed (market) preferences, it is necessary to rely on stated preferences of respondents in order to evaluate the economic value of health interventions as well to improve public health care interventions and make them more patients oriented. Also, this article explores the method of discrete choice experiment along with its applications in healthcare, which seeks to identify the marginal rate of substitution between relevant attributes of public healthcare intervention and its impact on the patients’ choice, hence enabling a broad application of the method.